2021
DOI: 10.1021/acsptsci.0c00216
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Inhibitors of SARS-CoV-2 3CL-Pro Enzymatic Activity Using a Small Molecule in Vitro Repurposing Screen

Abstract: Compound repurposing is an important strategy for the identification of effective treatment options against SARS-CoV-2 infection and COVID-19 disease. In this regard, SARS-CoV-2 main protease (3CL-Pro), also termed M-Pro, is an attractive drug target as it plays a central role in viral replication by processing the viral polyproteins pp1a and pp1ab at multiple distinct cleavage sites. We here report the results of a repurposing program involving 8.7 K compounds containing marketed drugs, clinical and preclinic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(131 citation statements)
references
References 63 publications
2
120
0
Order By: Relevance
“…Luteolin and apigenin, two flavones detected in the PGL extract, were found to be active on both HIV-1 enzymes, showing IC 50 values of 3.7 µM and 16.1 µM for RNase H activity and 6.5 µM and 22 µM for HIV-1 IN LEDGF-dependent activity, respectively, in agreement with our previous studies [38] although we found a lower degree of inhibition compared with ellagic acid and the control. Flavonoids are a class of natural compounds endowed with a broad spectrum of biological activities, including anti-SARS-CoV-2 activity [52] and promising anti-HIV-1 properties [53,54]. Interestingly, luteolin was found to be capable of inhibiting HIV-1 infection in Jurkat cells, showing better inhibition when added after HIV-1 infection, indicating that it exerts antiviral activity in the later stages of the HIV-1 lifecycle [55].…”
Section: Anti-hiv-1 Activity Of Pure Compounds Detected In Pgb Pgl and Pgpmentioning
confidence: 99%
“…Luteolin and apigenin, two flavones detected in the PGL extract, were found to be active on both HIV-1 enzymes, showing IC 50 values of 3.7 µM and 16.1 µM for RNase H activity and 6.5 µM and 22 µM for HIV-1 IN LEDGF-dependent activity, respectively, in agreement with our previous studies [38] although we found a lower degree of inhibition compared with ellagic acid and the control. Flavonoids are a class of natural compounds endowed with a broad spectrum of biological activities, including anti-SARS-CoV-2 activity [52] and promising anti-HIV-1 properties [53,54]. Interestingly, luteolin was found to be capable of inhibiting HIV-1 infection in Jurkat cells, showing better inhibition when added after HIV-1 infection, indicating that it exerts antiviral activity in the later stages of the HIV-1 lifecycle [55].…”
Section: Anti-hiv-1 Activity Of Pure Compounds Detected In Pgb Pgl and Pgpmentioning
confidence: 99%
“…In order to find drug candidates against SARS-CoV-2, we performed a large-scale x-ray crystallographic screen of M pro against two repurposing libraries containing 5953 compounds from the Fraunhofer IME Repurposing Collection and the Safe-in-man library from Dompé Farmaceutici S.p.A. ( 5 ).…”
mentioning
confidence: 99%
“…To ensure a high level of data integrity, only compounds with explicitly defined IC 50 values were selected, using a cut-off of 5 μM as minimum potency to define compounds as "actives". A third dataset consisted of a recently added repository generated within the "EXaSCale smArt pLatform Against paThogEns for Corona-Virus, Exscalate4CoV or E4C" project (CHEMBL4495564), containing activity data for ~ 8000 compounds from the primary screening against SARS-CoV-2 Main protease (Mpro) [30]. In this case, compounds were considered as actives if enzyme inhibition was at least 40%.…”
Section: Chembl Datasetsmentioning
confidence: 99%